2017
DOI: 10.1155/2017/4698371
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities to Learn for Teachers’ Self‐Efficacy and Enthusiasm

Abstract: The aim of this study was to identify opportunities to learn for teachers' motivational orientations. Motivational orientations are relevant characteristics of psychological functioning, which are important for the behavior of a teacher and mandatory for effective teaching. We focus on three domains: self-efficacy, subject-specific enthusiasm, and enthusiasm for teaching the subject. Selfefficacy covers the belief of an individual that he or she is capable of performing required behaviors to produce a desired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 87 publications
(183 reference statements)
1
34
1
6
Order By: Relevance
“…As the belief system of teachers is likely to change when they enter school practice [138], our results are at the moment only applicable to pre-service teachers. But since teachers' individual experiences during teacher education are an important contributor to professional development [82], this phase of teacher education is important for shaping the professional identity of teachers. This has also been shown in biodiversity contexts [139].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the belief system of teachers is likely to change when they enter school practice [138], our results are at the moment only applicable to pre-service teachers. But since teachers' individual experiences during teacher education are an important contributor to professional development [82], this phase of teacher education is important for shaping the professional identity of teachers. This has also been shown in biodiversity contexts [139].…”
Section: Discussionmentioning
confidence: 99%
“…While both variables refer to the individual's ability to perform behaviours, perceived behavioural control better captures the specific nature of teaching about topics, as self-efficacy is a more general trait than concentrated on one behaviour [79,80]. Prior studies found knowledge [81] and initial teacher education [82] as important antecedents of efficacy beliefs.…”
Section: Teaching Motivationmentioning
confidence: 99%
“…The connection between motivation, and different aspects of teaching and learning Biology was approved in numerous studies (e.g. Dyrberg, Treusch, & Wiegand, 2017;Jeno, Grytnes, & Vandvik, 2017;Mahler, Großschedl, & Harms, 2017).…”
Section: Based On Exploratory Factor Analysis Andmentioning
confidence: 99%
“…Self-efficacy among teachers has been shown to be related to their performance in relation to the teaching-learning process, as well as their emotional aspects, regarding emotional exhaustion and satisfaction towards work (Mahler, Großschedl, & Harms, 2017). A study with Korean teachers demonstrated that the sense of efficacy positively correlates with persistence, self-directedness, cooperativeness, and self-transcendence, acting as a protective resource against stress (Park et al, 2016).…”
Section: Discussionmentioning
confidence: 99%